PROSODIC FEATURES OF SPEECH FORMS OF ADDRESS IN ENGLISH DISCOURSE IN COMPARISON WITH DIFFERENCE INTERNATION LANGUAGES - Shaxnoza Artikova (Journals Park Publishing, 2022)
The results of the study showed that some prosodic indicators of regional speech have a tendency to gradually increase in the direction from North to South and vice versa.
Keywords: tendency to gradually increase,; prosodic features